1996
DOI: 10.2134/agronj1996.00021962003600060020x
|View full text |Cite
|
Sign up to set email alerts
|

Cover Crops Affect Sorghum Seedling Growth

Abstract: Recently killed cover crops often interfere with crop seedling growth. Controlled‐environment and field studies were conducted to characterize the nature and persistence of cover crop interference with sorghum [Sorghum bicolor (L.) Moench] seedling growth and to test several seed‐zone management practices that might alleviate detrimental effects. Germination, root and shoot length, and disease incidence of sorghum germinated at 25°C for 5 d in soil collected 2, 4, 7, 14, 23, and 32 d after killing cover crops … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
33
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(36 citation statements)
references
References 17 publications
3
33
0
Order By: Relevance
“…Too high biomass could have prevented the good emergence of wheat at seeding, or biomass decomposition in spring could have induced nitrogen immobilisation, due to high C/N ratio, linked to the lower proportion of legumes observed this year. These are two negative aspects of cover crop cultivation often mentioned in this context (Dabney et al, 1996;Fageria et al, 2005). Producing the highest possible cover crop biomass is thus not necessarily the objective in such systems.…”
Section: Effect On the Following Wheat Cropmentioning
confidence: 99%
“…Too high biomass could have prevented the good emergence of wheat at seeding, or biomass decomposition in spring could have induced nitrogen immobilisation, due to high C/N ratio, linked to the lower proportion of legumes observed this year. These are two negative aspects of cover crop cultivation often mentioned in this context (Dabney et al, 1996;Fageria et al, 2005). Producing the highest possible cover crop biomass is thus not necessarily the objective in such systems.…”
Section: Effect On the Following Wheat Cropmentioning
confidence: 99%
“…Similarly, Sharma-Poudyal et al (2016) found that increasing the time interval between herbicide application to a wheat cover crop and onion planting reduced the infection of onion roots by Rhizoctonia spp. Finally, Dabney et al (1996) reported that sorghum root disease incidence decreased when the time interval between spraying legume cover crops and planting sorghum was increased. These studies suggest that the time interval between termination of rye cover crops and corn planting may also be important.…”
mentioning
confidence: 99%
“…. Soil phytotoxicity during giant foxtail and com seedling recruitment was assessed with bioassays measuring effects of field soil on germination percentage and radicle growth (Dabney et al 1996).…”
Section: Methodsmentioning
confidence: 99%
“…Soil phytotoxicity during giant foxtail and corn seedling recruitment was assessed with bioassays (Dabney et al 1996). Forty giant foxtail seeds or 10 corn seeds were spaced in a line 10 cm from the top edge of two 25 cm by 38 cm sheets of germination paper moistened with 20 mL distilled deionized HiO.…”
Section: Soil and Weather Datamentioning
confidence: 99%
See 1 more Smart Citation